Microbial Community Degradation of Widely Used Quaternary Ammonium Disinfectants - Oh, Seungdae (American Society for Microbiology, 2014)
Benzalkonium chlorides (BACs) are disinfectants widely used in a variety of clinical and environmental settings to prevent microbial infections, and they are frequently detected in nontarget environments, such as aquatic and engineered biological systems, even at toxic levels. Therefore, microbial degradation of BACs has important ramifications for alleviating disinfectant toxicity in nontarget environments as well as compromising disinfectant efficacy in target environments. However, how natural microbial communities respond to BAC exposure and what genes underlie BAC biodegradation remain elusive. Our previous metagenomic analysis of a river sediment microbial community revealed that BAC exposure selected for a low-diversity community, dominated by several members of the Pseudomonas genus that quickly degraded BACs. To elucidate the genetic determinants of BAC degradation, we conducted time-series metatranscriptomic analysis of this microbial community during a complete feeding cycle with BACs as the sole carbon and energy source under aerobic conditions. Metatranscriptomic profiles revealed a candidate gene for BAC dealkylation, the first step in BAC biodegradation that results in a product 500 times less toxic. Subsequent biochemical assays and isolate characterization verified that the putative amine oxidase gene product was functionally capable of initiating BAC degradation. Our analysis also revealed cooperative interactions among community members to alleviate BAC toxicity, such as the further degradation of BAC dealkylation by-products by organisms not encoding amine oxidase. Collectively, our results advance the understanding of BAC aerobic biodegradation and provide genetic biomarkers to assess the critical first step of this process in nontarget environments.